2019
DOI: 10.1016/j.jshs.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of built environment on physical activity and obesity among children and adolescents in China: A narrative systematic review

Abstract: Highlights We systematically reviewed evidence regarding the impact of built environment on physical activity and obesity among children and adolescents in China. Twenty studies, including 16 cross-sectional, 3 longitudinal, and 1 descriptive studies, met the predetermined selection criteria and were included in the review. Availability and accessibility in proximity to greenspace, park, recreational facility, and sidewalks were found to be associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 50 publications
2
78
1
10
Order By: Relevance
“…In contrast, features such as the lack of bike lanes and high residential density are likely to be associated with childhood overweight and obesity. 109 …”
Section: Statementsmentioning
confidence: 99%
“…In contrast, features such as the lack of bike lanes and high residential density are likely to be associated with childhood overweight and obesity. 109 …”
Section: Statementsmentioning
confidence: 99%
“…China has the largest number of obese people and the prevalence of obesity in children and adolescents has been increasing [ 6 ]. By 2030, 49.5 million children will suffer from obesity, adversely affecting their physical and intellectual development [ 7 , 8 ]. Therefore, there is an urgent need to reduce both its prevalence and impact.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, the population density of China's megacities is much higher than that of many cities in Western countries, and the differences between urban built environments and culture may result in different research results. Taking population density as an example, academic circles have found relevant research results in China's megacities: some research results show that it is negatively correlated with adolescents' entertainment physical activity (27,28), or they show no correlation (29); another study found that it is negatively related to the leisure physical activities of adult women (30). Therefore, it is particularly important to re-examine the relationship between the built environment of megacities and the physical activity of residents.…”
Section: Introductionmentioning
confidence: 99%